Symptomatic improvement and functional outcome of discectomy in Prolapsed Lumbar Intervertebral Disc - Yadav, Ram Kumar; Lakhey, Rajesh Bahadur; Paudel, Sushil; Kafle, Dinesh; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Herniated lumbar disc is one of the common causes of back pain and sciatica in our clinical practice. Discectomy provides rapid relief of back pain and radicular pain. Few studies have been done in our setting to look for the outcome of discectomy. The purpose of this study was to assess the outcome of discectomy. METHODS: This prospective observational study was carried out in Tribhuvan University Teaching Hospital, Kathmandu, from January 2018 to June 2019. Total of 31 patients with prolapsed disc underwent minimal invasive open lumbar discectomy. They were followed for six months and outcomes evaluated with Visual analogous scale score and Modified Oswestry disability index questionnaire and the overall response for surgery was evaluated with Modified Macnab’s criteria. RESULTS: Out of 31 patients, 19 were male and 12 were females, with mean age of 35 years. Preoperative mean VAS for leg pain and back pain was 7.32±1.14 and 7.29±1.13 respectively improving subsequently in later follow up at 2 weeks and 3 months. At 6 months, mean Visual analogous scale was 0.45±0.57 and 0.48±0.57(P <0.001) respectively for leg pain and back pain. Mean preoperative Oswestry disability index score was 53.28±12.18 that improved to 23.15±8.02 and 9.15±5.0 (P<0.001) at 3 months and 6 months follow up respectively. At final follow up the Modified Macnab’s Criteria was excellent in 13 cases, good in 16 cases and fair in 2 cases. CONCLUSION: Excision of the offending herniated disc to decompress the nerve root provides rapid relief of symptoms and improved quality of life.